2018
DOI: 10.1590/0102-672020180001e1343
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Remission Rate in Different Bmi Grades Following Roux-en-Y Gastric Bypass

Abstract: Background: Type 2 diabetes mellitus has a high long-term remission rate after laparoscopic Roux-en-Y gastric bypass (LRYGB), but few studies have analyzed patients with BMI<35 kg/m2. Aim: To compare glycemic control after LRYGB between BMI 30-35 kg/m2 (intervention group or IG) and >35 kg/m2 patients (control group or CG) and to evaluate weight loss, comorbidities and surgical morbidity. Methods: Sixty-six diabetic patients (30 in IG group and 36 in CG group) were submitted to LRYGB. Data collected annually a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…One study found that a composite scoring system (e.g., age, BMI, C‐peptide level, and duration of T2D) predicted response in glycemic markers to bariatric surgery . In another study, higher baseline BMI was associated with a greater improvement in T2D after RYGB . In any event, “remission” is the proper terminology as opposed to “cure,” since overt T2D returns in over half of these patients in less than 10 years .…”
Section: Executive Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that a composite scoring system (e.g., age, BMI, C‐peptide level, and duration of T2D) predicted response in glycemic markers to bariatric surgery . In another study, higher baseline BMI was associated with a greater improvement in T2D after RYGB . In any event, “remission” is the proper terminology as opposed to “cure,” since overt T2D returns in over half of these patients in less than 10 years .…”
Section: Executive Summarymentioning
confidence: 99%
“…However, the preponderance of studies in patients with class‐I obesity have focused on the clinical benefits of bariatric procedures in those patients with T2D. A substantial number of RCTs and cohort interventional trials have demonstrated that bariatric surgical procedures can effectively result in sustained improvement in glycemic control concomitant with reductions in diabetes medications in patients with BMI 30 to 34.9 kg/m 2 . Multiple meta‐analyses that specifically examined bariatric surgery outcomes in patients with BMI < 35 kg/m 2 have been published and support clinical benefits regarding glycemic control and weight loss .…”
Section: Executive Summarymentioning
confidence: 99%
“…Wang X et al (2016) [ 15 ] recorded a male participation of 42.8%, and Nguyen KT et al (2015) [ 18 ] noted a near-equal representation of 48.5% of males. Notably, several studies like Wallenius V et al (2015) [ 12 ], Seki Y et al (2022) [ 13 ], Coelho D et al (2018) [ 16 ], Ikramuddin S et al (2016) [ 17 ], and Petry TZ et al (2015) [ 19 ] did not specify the gender ratio. Study designs varied, with some following a prospective approach, some being retrospective, while others were randomized clinical trials or cohort studies.…”
Section: Reviewmentioning
confidence: 99%
“…The surgery was found to be notably effective for weight loss and improving glycemic control, especially for patients with higher BMI. Two studies, Coelho D et al [ 16 ] and Ikramuddin S et al [ 17 ], explored the long-term impacts of RYGB. Both studies highlighted the efficacy of RYGB in achieving diabetes treatment goals, with the latter also pointing out the risks associated with the procedure over time.…”
Section: Reviewmentioning
confidence: 99%
“…Currently the two most commonly performed bariatric surgeries in the world are Roux-en-Y gastric bypass (BGYR) and vertical gastrectomy (GV) 2 . Despite many controversies regarding the comparison of techniques, both are safe and effective, however with slightly different comorbidities remission rates 3 , 6 , 18 .…”
Section: Introductionmentioning
confidence: 99%